Efforts of Ahle Hadith scholars to Spreading Islamic preaching - Khola Hafiz Abdul Waheed Fatih Muhammad; Dr. Latifah Abdulaziz ALmayouf (jihat-ul-islam, 2026)
The research deals with an important subject of the Islamic preaching, the Efforts of Ahle Hadith scholars to Spreading Islamic preaching; The Ahl al-Hadith movement is the oldest Islamic movement in the Indian subcontinent. It was based on following the Qur’an and Sunnah in light of the understanding of the righteous predecessors. Their history goes back to the first Islamic era in the fourth century AH. The new era began in the era of Ahmad al-Sirhindi, and the movement strengthened during the era of the sons of Shah Waliullah Dehlawi. And strength increased during the era of Shah Ismail al-Shahid. The scholars of Ahl al-Hadith have made great efforts in spreading the right monotheism and the Sunnah, fighting polytheism and heresies, abandoning sectarian fanaticism and returning to the Qur’an and Sunnah, implementing the Islamic legal system in the country, also developing the Salafi curriculum in education, establishing religious schools, libraries, Islamic researcher centers, and others. Nowadays, the Ah al-Hadith scholars have kept pace with technological development, creating websites, electronic libraries, and research centers, making it easier for people to benefit from correct Islamic knowledge at any time.